Atypical teratoid/rhabdoid tumor with retained INI1 (SMARCB1) expression and loss of BRG1 (SMARCA4). Issue 3 (21st December 2017) - Bookhout, Christine; Bouldin, Thomas W.; Ellison, David W.
Abstract : Atypical teratoid/rhabdoid tumor (AT/RT) is a rare, highly aggressive malignancy of the central nervous system (CNS) usually diagnosed in infancy or childhood, most often characterized by loss of expression of the SMARCB1 gene product integrase interactor 1 (INI1) protein. We report a case of AT/RT in a 3 month old boy with retained expression of INI1 by immunohistochemistry. Additional testing demonstrated loss of expression of the SMARCA4 gene product Brahma‐related gene 1 (BRG1) protein by immunohistochemistry, confirmed by next generation sequencing showing a nonsense mutation in SMARCA4. This case illustrates that positivity for INI1 does not rule out a diagnosis of AT/RT, and additional testing, including BRG1/ SMARCA4 analysis, is warranted in cases where clinical suspicion is high.